1986
DOI: 10.1007/bf00046255
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in marine triclads and polyclads (Turbellaria)

Abstract: From an analysis of chromosomal mutations in seven species among five genera of marine triclads and polyclads, three different types of mechanisms of such mutations are identified : 1) rearrangement involving the centromere such that its position is changed, 2) rearrangement of whole chromosome arms, and 3) Robertsonian mechanisms . These mechanisms are the same as those reported for freshwater turbellarians, but aneuploidy and polyploidy, which are common in freshwater species, were not detected in these mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Speciation events associated with such chromosome rearrangements have been suggested for other planarian genera (Benazzi, 1982) as well as for other turbellarian groups (Curini-Galletti, Puccinelli, & Martens, 1985;Galleni & Puccinelli, 1986).…”
Section: From a Morphological Point Of View Autapomorphies For Eachmentioning
confidence: 86%
“…Speciation events associated with such chromosome rearrangements have been suggested for other planarian genera (Benazzi, 1982) as well as for other turbellarian groups (Curini-Galletti, Puccinelli, & Martens, 1985;Galleni & Puccinelli, 1986).…”
Section: From a Morphological Point Of View Autapomorphies For Eachmentioning
confidence: 86%
“…In the second scenario, we could face a possible case of biogeographical sympatric speciation due to a chromosomal rearrangement, with a concomitant parallel dispersion over the same fluvial basins. Speciation due to chromosomal rearrangements has been proposed to take place in other planarian genera (Benazzi 1982;Leria et al 2018) as well as in several turbellarian groups (Curini-Galletti et al 1985;Galleni and Puccinelli 1986). On the other hand, regardless of the taxonomical status of D. hepta, given its external morphological similarity to D. benazzii and their spatial distribution, one could wonder whether they are able to intercross and if they do it naturally.…”
Section: Introductionmentioning
confidence: 99%
“…De Vries (1984) reported on a similar case for freshwater planarians in which the type of epithelium in the bursal canal depended upon the state of maturity of the animals. Galleni, Nigro & Puccinelli (1984) and Galleni & Puccinelli (1986) reported on the chromosome complement of P. dohrni collected near Pisa, Italy. However, examination of four specimens from their sample (see Material examined) revealed that the animals actually belong to P. lobata.…”
Section: Remarksmentioning
confidence: 99%